(3EOGQI GdehGQO GdHTQjI (B/s - (3MGQhT, fhQ GdOjfs ((3GdLRGFQ(B: s (3OGQ GdCeI ddWHGYI ddfTQ hGdJhRjY(B, s, 2016)
(3eaghe hCgejI EOGQI GdehGQO GdHTQjI,GdJWhQ GdJGQjNj deaghe heeGQSI EOGQI GdehGQO GdHTQjI,ESJQGJjLjI EOGQI GdehGQO GdHTQjI,JMdjd hJhUja GdhXGFa,Jchjf hJOQjH hJWhjQ GdehGQO GdHTQjI,Jbjje GdhXGFa,Jbjje GdCOGA, fXGe GdCLhQ hGdQhGJH,JMajR GdehGQO GdHTQjI,GdeSGQ GdhXjaj,EfgGA GdNOeGJ,JgjFI Gdbje hGdKbGaI OGNd GdefXeI,GdGJLGgGJ GdeYGUQ aj EOGQI GdehGQO GdHTQjIGdJWhjQ GdJfXjej,EOGQI GdLhOI GdTGedI,GdEOGQI HGdeYQaI hGdEOGQI HGdeYdheGJ,GJLGgGJ eYGUQI CNQi,JfejI GdehGQO GdHTQjI,EOGQI GdehGQO GdHTQjI(B:(3JWHjb Ydi GdLRGFQ ef NdGd bGfhf GdhXjaI GdYehejI (B06-03(3,GdZjGH(B:(3OQGSI fXQjIs
(3HjHdjhZQGajG(B: (3U(B. 279-285s
Keywords: (3EOGQI GdCaQGOs